Foreign Direct Investment and Sustainable Development in the New EU Member States: Environmental Aspects; Bezposŕednie inwestycje zagraniczne a zroẃnowazȯny rozwoj́ w nowych krajach członkowskich Unii Europejskiej. Aspekty ochrony sŕodowiska - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2011)
The aim of this paper is to examine the potential impact of foreign investors' activities on the environment of the new European Union's Member States and discuss a role of a common environmental policy and member states' policies towards foreign investors. The analysis embraces three new EU countries, namely the Czech Republic, Poland and Slovakia. The scope of the analysis are years 1997- 2007. The subject of the analysis is the sector and branch structure of FDI stock in the new EU Member States with special reference to FDI located in pollution-intensive industries which are selected according to the UNCTAD classification. Both the OECD and national data base of statistics is used to calculate the share of foreign investors' involvement in pollution-intensive activities in the new UE Member States. The research results show that as yet there has been no empirical evidence that FDI has a particularly negative impact on the natural environment in the new EU Member States. – – Celem artykułu jest zbadanie potencjalnego wpływu działalnosći inwestoroẃ zagranicznych na sŕodowisko w nowych krajach członkowskich Unii Europejskiej (UE) oraz ocena roli wspoĺnej polityki ochrony sŕodowiska UE i polityki wobec inwestoroẃ zagranicznych w tym zakresie. Analiza obejmuje trzy nowe kraje członkowskie UE, tj. Czechy, Polske i Słowacje. Zakres czasowy analizy to lata 1997-2007. Przedmiotem analizy jest struktura sektorowa i branzȯwa skumulowanych bezposŕednich inwestycji zagranicznych (BIZ) w tych krajach, ze szczegoĺnym uwzglednieniem BIZ ulokowanych w przemysłach intensywnie zanieczyszczajacych sŕodowisko. Do okresĺenia tych przemysłoẃ wykorzystano klasyfikacje UNCTAD. W analizie statystycznej wykorzystano baze danych OECD oraz statystyki narodowe. Wyniki badanẃskazuja, zė - jak dotychczas - nie ma empirycznych dowodoẃ, izḂIZ maja szczegoĺnie negatywny wpływ na sŕodowisko w nowych krajach członkowskich UE.
Keywords: 330